Pergeseran Sufisme Tradisional Ke Urban Sufisme dalam Korporasi Sub-Urban - Yuzki Arifian Nawafi, Ahmad (IAIN Kendari, 2025)
This study examines the shift from traditional Sufism to urban Sufism in the context of a sub-urban corporation, with a focus on PT Mayangkara Group in Blitar. The research found that the implementation of spiritual values in this company occurred through seven phases, starting from the informal introduction of religious values in the 1970s to the formation of a more structured spiritual habitus in 2015. These phases demonstrate the company's efforts in integrating Islamic values, such as discipline, honesty, trustworthiness and responsibility, in various operational aspects, including recruitment, selection, training and compensation. The research also highlights the application of normative values, such as the teachings of the Qur'an and Hadith, as well as the philosophy of Pancasila, which encourage a balance between worldly performance and spirituality. The results show that the synergy between spiritual values and work ethic creates a harmonious and productive work environment. In building the synergy of spiritual values and work ethic values through human resources, five patterns of habitus formation were found in the company environment. Among them are recruitment, selection, performance appraisal, training and development, and compensation. The program focuses on the balance between worldly and afterlife life, in accordance with the company's vision: